Woman Linguistic Features Reflected by Margaret Thatcher in the Film Iron Lady. - AULYA, SITI DARA NIRMALA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Aulya, Siti Dara Nirmala. 2014.Woman Linguistic Features Reflected by Margaret Thatcher in the Film Iron Lady. Study Program of English, Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya. Supervisor : Emy Sudarwati; Co –Supervisor : Ida Puji LestariKeywords : Woman Linguistic Feautres, Margaret Thatcher, Iron Lady.The linguistics feature of women speech is one of the topics discussed in Sociolinguistics. In this study, the writer concerns to find out the linguistic features of woman found in the film  Iron Lady, the mostly used linguistic features in the utterances produced by Margaret Thatcher of the film Iron Lady, and the purpose of using these linguistic features.This research is a descriptive qualitative as it means to gain  understanding about woman speech style in the film Iron Lady. The data were taken from the utterances of the main character of this movie. The utterances were classified and analyzed into 10 (ten) linguistic features by Lakoff (1975) then calculated all to find out the mostly linguistic features used by Margaret Thatcher and drew it in conclusion.The result of analysis revealed that there were 114 utterances spoken by Margaret Thatcher which can be classified into 8 (eight) woman’s linguistic features. There were 20 lexical hedges and fillers, only 2 (two) tag questions, 8 (eight) rising intonations, 30  adjectives, 33 intensifiers, 14 superpolite forms, 3 (three) expression expressed avoidance of strong swear words, 4 (four) emphatic stress spoken by the main character in the film Iron Lady.The writer hopes that the future researchers can combine more linguistic features which are proposed by some experts. The next researchers can identify about characteristics of a woman deeply. It is better if the future researchers can compare the linguistic features from some experts who talk by using another theory about women’s language.